2009 42nd Hawaii International Conference on System Sciences 2009
DOI: 10.1109/hicss.2009.270
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence between Employee Education and R and D Investment in Impacting IT Firm Performance

Abstract: An educated workforce is critical for IT firms ability to innovate and compete in the market. Surprisingly, there is very little research on how education contributes to the profitability of IT firms and how educated employees contribute to a firms research and development activities. Using theories from human capital literature, we propose a model to measure how education impacts firm profits in IT industries and how the relation is moderated by a firms R&D investments. Our results suggest that education is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…An educated workforce, especially in the IT-Department is critical for the ability of a company to innovate and compete in the market. Surprisingly, there is very little research on how education contributes to the profitability of IT firms and how employees contribute to research and development activities (Banker, Wattal, Liu, & Ou, 2009). In addition human resources management is a very complex domain on its own and a SLR conducted in March 2014 has shown that the the problem of skill shortage in companies can only be solved if further scientific areas, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…An educated workforce, especially in the IT-Department is critical for the ability of a company to innovate and compete in the market. Surprisingly, there is very little research on how education contributes to the profitability of IT firms and how employees contribute to research and development activities (Banker, Wattal, Liu, & Ou, 2009). In addition human resources management is a very complex domain on its own and a SLR conducted in March 2014 has shown that the the problem of skill shortage in companies can only be solved if further scientific areas, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…But, an educated workforce, especially in the IT-Department is critical for the ability of a company to innovate and compete in the market. Surprisingly, there is very little research on how education contributes to the profitability of IT firms and how employees contribute to research and development activities (Banker, Wattal, Liu, & Ou, 2009).…”
Section: Skill Shortage In It Departments and The Impact For Companiesmentioning
confidence: 99%